Growth, yield and nutrient content of blackgram (Vigna mungo) as influenced by levels of phosphorus, sulphur and Phosphorus Solubilizing Bacteria - Mir, AH; Lal, SB; Salmani, M; Abid, M; Khan, I (SAARC Journal of Agriculture, 2014)
A field experiment was conducted at Allahabad Agricultural Institute- Deemed University, Allahabad to study the effect of levels of phosphorus, sulphur and Phosphorus Solubilizing Bacteria (PSB) on growth, yield and nutrient content of blackgram for consecutive two years 2004 and 2005. The crop growth parameters viz., plant height, number of nodules and number of leaves per plant, yield and nutrient content increased significantly with the application of high levels of phosphorus, sulphur with or without bio-fertilizer inoculation. Application of 60 kg P2O5 ha-1 recorded maximum plant height (49.9 cm), number of leaves plant-1 (50.8), number of nodules plant-1 (27.8), haulm yield (28.9 q ha-1), grain yield (8 q ha-1) and phosphorus, sulphur and protein content of grain (0.356 %, 0.253% and 22.64%, respectively) as compared to lower levels. Application of Sulphur @ 40 kg ha-1 recorded maximum plant height (47.31 cm), number of leaves plant-1 (49.80), number of nodules plant-1 (25.58), haulm yield (28.80 q ha-1), grain yield (7.92 q ha-1) and phosphorus, sulphur and protein content (0.295 , 0.281 and 21.79%, respectively). Inoculation of blackgram seeds with phosphorus solubilizing bacteria recorded slightly higher grain yield (7.49 q ha-1) as compared to no inoculation (7.39 q ha-1). DOI: http://dx.doi.org/10.3329/sja.v11i1.18370 SAARC J. Agri., 11(1): 1-6 (2013)